COVID-19 mitigation and effects on food safety - Mutua, Florence K.; Kang'ethe, Erastus K.; Grace, Delia (International Livestock Research Institute, 2021)
COVID-19 is not transmitted through food, however, measures put in place to contain its spread disrupted food systems in many ways. We interviewed experts working on food safety in countries within East Africa, to understand the effects the pandemic had on safety of foods consumed in the region. Several issues were observed, and these were related to: the bulk purchasing of food products, their handling, and storage; the rush to make purchases and supply of expired products or those nearing their expiry periods; the delay of food and feed trucks especially at border points; and the working in shifts, which, given the limited staff, reduced the capacity of food businesses to undertake the usual inspection. Future interventions should consider the negative impacts arising from enforcement of mitigation measures. A One Health approach would promote this.